Analysis of Alien Species Invasion in Marine Debris in Palu Bay, Central Sulawesi - Roni Hermawan; Anita Treisya Aristawati; Eka Aji Pramita; Mubin Mubin; Rahmi Fitrawati; Finarti Finarti; Mohamad Akbar; Renol Renol; Alismi M Salanggon; Radhiyatul Ula (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Marine debris provides habitat for several species. These species attach and carried (rafting) marine debris in all directions following the ocean currents. When stranded, these alien species will quickly develop because they have high survival and adaptation capabilities, these alien species will cause economic, ecological and social impacts. This research begins with a survey of the presence of marine debris that attached by alien species on coast of Palu Bay, then observations on the marine debris such as: size, weight, observations on alien species such as: type, size, colony size, ability to spread and survive, impact category based on literature. The aim of this study was to identify the types of alien species carried by marine debris in Palu Bay. Calculating the amount of alien species carried by marine debris in Palu Bay. Based on the analysis, there are 3 alien species on the coast of Palu Bay. Lepas sp were 247 individuals, then Isognomon sp with 124 individuals and Saccostrea cuccullata d for 36 individuals. The species were found on wood, iron, coconut, PVC pipes, bamboo, nets and boat ropes as substrates.